World Bank Group’s engagement in Kazakhstan - Ivakhnenko, Aleksei; Hnát, Pavel, 1981-; Bok, Martin; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
Kazakhstan has experienced rapid economic growth and ongoing modernisation since independence, but it still faces structural weaknesses that slow its progress toward sustainable development. This thesis examines how the World Bank’s engagement supports Kazakhstan’s sustainable development agenda and contributes to the achievement of the SDGs. The analysis is based on strategic documents and project materials evaluation. The findings show that World Bank projects make an important contribution to improving energy efficiency, managing water resources, and restoring degraded landscapes, while also strengthening institutional capacities in key sectors. At the same time, their overall effect is limited by persistent structural challenges and differences in institutional readiness. The thesis concludes with recommendations on how future cooperation can more effectively promote economic diversification, increase resilience to climate risks, and support Kazakhstan’s long-term development goals.
Vedoucí práce: Pavel Hnát
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses